EFEKTIVITAS MODEL PEMBELAJARAN TEMATIK TERPADU UNTUK MENINGKATKAN PENGETAHUAN DAN SIKAP MULTIBUDAYA MAHASISWA DI UNIVERSITAS PERSADA INDONESIA – YAI JAKARTA (Lembaga Penerbitan Universitas Esa Unggul, 2018)
Abstract The focus of this research is to know the effectivity of integrated thematic learning model application for increasing students’ multicultural knowledge and attitude. The sample of the research are students’ of Philosophy and Ethical Communication in Faculty of Communication Science Persada Indonesia University – YAI Jakarta. The method of research used an action research, this method uses for increasing students’ multicultural knowledge and attitude. Data of research are taken by using test and non-test. Technique of data analysis is to know the difference of research result by using test. The research begins by doing pre-test of students’ multicultural knowledge and attitude. Result of the research indicates; 1) There is an increase of students’ multicultural knowledge and attitude between the first stage post-test and pre-test; 2) There is an increase of students’ multicultural knowledge and attitude between the second stage post-test and first stage post-test; 3) The increase of students’ multicultural knowledge and attitude means that integrated thematic learning model used effectively; 4) There is an increase of teacher college competence. This research recommends to civitas academica of Persada Indonesia University – YAI Jakarta to use integrated thematic learning model to all subject learning. Keywords: multicultural, integrated thematic learning model. Abstrak Fokus penelitian ini adalah untuk mengetahui efektivitas penerapan model Pembelajaran Tematik Terpadu untuk meningkatkan pengetahuan dan sikap multikultural siswa. Sampel penelitian adalah mahasiswa Fisika Filsafat dan Etika di Fakultas Ilmu Komunikasi Universitas Persada Indonesia - YAI Jakarta. Metode penelitian menggunakan penelitian tindakan, metode ini digunakan untuk meningkatkan pengetahuan dan sikap multikultural siswa. Data penelitian diambil dengan menggunakan tes dan non-tes. Teknik analisis data adalah untuk mengetahui perbedaan hasil penelitian dengan menggunakan tes. Penelitian dimulai dengan melakukan pra-tes pengetahuan dan sikap multikultural siswa. Hasil penelitian menunjukkan; 1) Ada peningkatan pengetahuan dan sikap multibudaya siswa antara tahap pertama post-test dan pre-test; 2) Ada peningkatan pengetahuan dan sikap multibudaya siswa antara tahap kedua post-test dan tahap pertama post-test; 3) Peningkatan pengetahuan dan sikap multikultural siswa berarti bahwa Pembelajaran Tematik Terpadu yang digunakan secara efektif; 4) Ada peningkatan kompetensi guru perguruan tinggi. Penelitian ini merekomendasikan kepada civitas akademika Universitas Persada Indonesia - YAI Jakarta untuk menggunakan model Pembelajaran Tematik Terpadu untuk semua mata pelajaran. Kata kunci: multibudaya, model pembelajaran tematik terpadu.